METHODS OF TEACHING COMMUNICATION IN HIGHER EDUCATIONAL INSTITUTIONS - Akbarova Feruza Tulkunjonovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article considers the specifics and methods of teaching Russian as a non-native language in a technical university.